Defining Mastectomy Skin Flap Necrosis: A Systematic Review of the Literature and a Call for Standardization. Issue 5 (2nd March 2022) - Oleck, Nicholas C.; Gu, Cindy; Pyfer, Bryan J.; Phillips, Brett T.
Abstract : Background: Mastectomy skin flap necrosis following breast reconstruction may lead to wound dehiscence, infection, implant exposure, and reconstructive failure. The absence of a standardized definition for it has led to variation in estimated incidence, from as low as 2 percent to greater than 40 percent. The authors systematically reviewed the literature on mastectomy skin flap necrosis to characterize existing definitions and provide a framework for future classification. Methods: A systematic review of the PubMed and Cochrane databases identified studies reporting a discrete definition of mastectomy skin flap necrosis and corresponding outcomes in breast reconstruction. Provided definitions were extracted, categorized, and comparatively analyzed. Results: Fifty-nine studies met inclusion criteria, with a combined total of 14, 368 patients and 18, 920 breasts. Thirty-four studies (57.6 percent) reported mastectomy skin flap necrosis solely as a function of total breasts, and 11 (18.6 percent) reported mastectomy skin flap necrosis solely as a function of total patients. Only 14 studies (23.7 percent) provided two separate rates. The overall rate of mastectomy skin flap necrosis was 10.4 percent (range, 2.3 to 41.2 percent) and 15.3 percent (range, 4.7 to 39.0 percent), when reported per breast or per patient, respectively. Studies were categorized by mastectomy skin flap necrosis definition, including intervention ( n = 33), depth ( n = 20), area ( n = 4), and timing ( n = 2). Mastectomy skin flap necrosis rates were highest in studies defining necrosis by depth (15.1 percent), followed by intervention (9.6 percent), timing (6.4 percent), and area (6.3 percent). Necrosis rates among studies defining mastectomy skin flap necrosis by intervention, depth, and area were found to be statistically different ( p < 0.001) Conclusions: Reported mastectomy skin flap necrosis definitions and outcomes vary significantly in the existing literature. For accurate characterization and quantification, a clear, simplified, consensus definition must be adopted.